Pelatihan Dan Pengembangan Sumber Daya Manusia - Nurruli Fatur Rohmah (Intizam, Jurnal Manajemen Pendidikan Islam, 2018)
Human Resources have a major role in every organization's activities. Although supported by facilities and infrastructure, as well as promising funding sources, but without reliable HR support, organizational activities will not be resolved properly. This shows that HR is the main key that must be considered with all its needs. To produce maximum goals, it is necessary to know the Basics of HR Training and Development, Analysis of Training Needs, Factors Affecting, Evaluation and Methods of Training and HR Development so that it can be adapted to the strength of an organization. Training is followed by non-managerial in a systematic process to obtain / improve knowledge, skills, and change one's behavior. Stages of training and development: Assessment of training needs, development of training programs, and evaluation of training programs. Analysis of HR training and development needs is needed: Organizational Analysis, Work, Individual Needs and Targeting. The factors that influence training and development: Who participates in the program, who is the trainer / instructor, what media is used, what level of learning, the principles of training needed, the principles of learning used, and where the program will be implemented. The program is evaluated can use survey methods, case studies, experiments, and test methods. HR Training and Development Methods are: On the job (training in the workplace) and off the job (training outside the workplace) including simulation and presentation of information.